2023
DOI: 10.1039/d3ce00312d
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of defect-induced pristine α-NaCe(WO4)2: a novel material for solid state lighting and gas sensing

Abstract: Triclinic NaCe(WO4)2 with oxygen monovacancy and divacancy has been successfully prepared by a facile cetyltrimethyl ammonium bromide (CTAB) assisted hydrothermal technique. X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…The binding energy data of all elements were adjusted with respect to the binding energy (∼284.6 eV) of surface-adsorbed atmospheric C 1s. 14 The survey scans for all the synthesized samples are presented in Fig. S8 of the ESI,† while the high-resolution spectra of Mo, Ce, and O are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The binding energy data of all elements were adjusted with respect to the binding energy (∼284.6 eV) of surface-adsorbed atmospheric C 1s. 14 The survey scans for all the synthesized samples are presented in Fig. S8 of the ESI,† while the high-resolution spectra of Mo, Ce, and O are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, Lin et al reported the V O -induced gas sensing activity of NaBi(MoO 4 ) 2 nanomaterials, 20 while our recent study demonstrated the NH 3 -sensing ability of NaCe(WO 4 ) 2 . 14 We herein also identify acetone-sensing ability in NaCe(MoO 4 ) 2 nanostructures, with V O and 2V O playing crucial roles in determining the sensitivity. To the best of our knowledge, this is the first report on the acetone-sensing ability of NaCe(MoO 4 ) 2 .…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The sensing mechanism of metal oxide sensors typically involves changes in electrical properties arising from interactions between the target gas and the surface of the sensing material. 34,48 In the case of the WO 3 sensor, a considerable quantity of oxygen molecules in the air atmosphere adhere to the surface of the sensing film, capturing free electrons from the WO 3 conduction band and generating chemisorbed oxygen species (O 2 − , O − , and O 2− ) through the following reactions eqn (3)–(6), depending on the operation temperatures. 49 In this work, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%